1986
DOI: 10.1021/ja00268a044
|View full text |Cite
|
Sign up to set email alerts
|

A novel cyclophane. Host-guest complexation and selective inclusion of aromatic guests from nonaqueous solution

Abstract: Asymmetric Reduction of Benzoylformic Ester to Methyl Mandelate ( S )or (R)-18. GeneralProcedure for 20-50-mg Scale. An ampule (2 mL) containing magnesium perchlorate (Mg(CIO,),-l .5 H 2 0 , 1 .O equiv) sealed with a small rubber septum was evacuated and flushed with argon several times. Methyl benzoylformate (1 .O equiv) was injected via syringe, followed by a solution of the 1,4-dihydropyridine (1.0 equiv) in freshly distilled acetonitrile (1 mL). The ampule was kept in the dark and the reduction allowed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…15 Cyclophanes have also been employed as selective catalysts, as auxiliaries in asymmetric synthesis, 16 as catalysts that simulate enzymatic functions, 17 in supramolecular chemistry, 18 in optoelectronic devices, 19,20 as precursors of nonlinear optical materials, 21 and in the preparation of artificial receptors. 22,23 The occurrence of transannular interactions 9,10 in cyclophanes has been detected not only by photoelectrons spectroscopy and by electronic spin resonance (ESR) 24,25 but also by other spectroscopic analyses such UV−vis and NMR. 26 These transannular interactions between the aromatic decks give a unique π-electron system, which is present not only in double-deck systems but also in multilayered [2 n ]cyclophanes.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Cyclophanes have also been employed as selective catalysts, as auxiliaries in asymmetric synthesis, 16 as catalysts that simulate enzymatic functions, 17 in supramolecular chemistry, 18 in optoelectronic devices, 19,20 as precursors of nonlinear optical materials, 21 and in the preparation of artificial receptors. 22,23 The occurrence of transannular interactions 9,10 in cyclophanes has been detected not only by photoelectrons spectroscopy and by electronic spin resonance (ESR) 24,25 but also by other spectroscopic analyses such UV−vis and NMR. 26 These transannular interactions between the aromatic decks give a unique π-electron system, which is present not only in double-deck systems but also in multilayered [2 n ]cyclophanes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The intrinsic structural features of [2 n ]cyclophanes make them attractive probes to investigate and to comprehend the interplay between strain versus aromaticity, the role of transannular effects ( through-bond and through-space interactions), the effects of substituents in transannular π–π interactions, , chemical shifts in aromatic systems, intramolecular charge transfer processes, and transannular reactions . Cyclophanes have also been employed as selective catalysts, as auxiliaries in asymmetric synthesis, as catalysts that simulate enzymatic functions, in supramolecular chemistry, in optoelectronic devices, , as precursors of nonlinear optical materials, and in the preparation of artificial receptors. , The occurrence of transannular interactions , in cyclophanes has been detected not only by photoelectrons spectroscopy and by electronic spin resonance (ESR) , but also by other spectroscopic analyses such UV–vis and NMR . These transannular interactions between the aromatic decks give a unique π-electron system, which is present not only in double-deck systems but also in multilayered [2 n ]cyclophanes …”
Section: Introductionmentioning
confidence: 99%
“…Compared w ith the situation of the intra-cavity benzene in the crystal structure of 2 (figure 2), a reduced affinity of benzene tow ard host 3 is to be expected. Accordingly, whereas cyclophane 1 (as quaternary ammonium derivative) binds benzene in aqueous solution (Diederich et al 1985), no evidence for 1:1 host-guest com plexation by 3 in solution has been reported (Saigo et al 1985(Saigo et al , 1986. Nevertheless, packing motifs from crystalline benzene can still be detected in the structural organization of this complex.…”
Section: Resultsmentioning
confidence: 98%
“…In the same year, Saigo et al (1985Saigo et al ( , 1986 reported th a t cyclophane 3 forms a crystalline 1: 1 complex (4) w ith benzene, and the X -ray crystal structure analysis showed th a t the guest is located between two host molecules. Later, Brown et al (1989) found th a t the hexaoxacyclophane 5 forms a 1:1 molecular complex (6) in which benzene is encapsulated in the macrocyclic cavity.…”
Section: Resultsmentioning
confidence: 99%